The effect of using organic fertilizers for enhancing the production and quality of peaches class may flower (Latakia University Journal -Biological Sciences Series, 2019)
The study was conducted in a farm in Tartous, during the years (2016) on the peach trees of The research was carried out in tartous governorate on peach trees, class may flower at the age of 12 years and at planting distances of 5x5 meters, for studying the effect of fertilizing buy using some organic fertilizers of marine origin regarding the quantity of production during the season of growing for the year 2018, through using marine algae extracts-Ancosiwed under concentration of 0.50 ml , Marin under concentration of 0.50 ml and Life green under concentration of 4.5g/l through spaying of total greenery , in addition to the soil with fertilizing basically the soil -The most important results that have been reached following: - The coefficients of soil Marin and soil Life increased the weight and size of the fruit , in addition to that the rest of the other coefficients surpassed on the control at average of the fruit size and weight. - The common Life coefficients and the soil life coefficients were featured by giving the best results for most of the chemical characteristic of the ripe fruit . نفذ البحث في محافظة طرطوس على أشجار الدراق صنف May flower بعمر 12 عاماً وبمسافات زراعة 5X5 متر، لدراسة تأثير التسميد ببعض المخصبات العضوية ذات المنشأ البحري في نوعية وكمية الإنتاج خلال موسم النمو لعام2018  ، وذلك باستخدام مستخلصات الطحالب البحرية انكوسيويد بتركيز 0.50 مل\ل و مارين بتركيز 0.50 مل\ل و لايف غرين بتركيز4.5 غ\ل رشا على المجموع الخضري واضافة للتربة مع تسميد أرضي أساس. وفيما يلي أهم النتائج المتحصل عليها: • زادت المعاملات مارين ارضي ولايف ارضي من وزن وحجم الثمرة، كما تفوقت بقية المعاملات الأخرى على الشاهد في متوسط وزن الثمرة وحجمها.• تميزت المعاملات لايف مشترك ولايف ارضي بأنها أعطت أفضل النتائج بالنسبة لأغلب الصفات الكيميائية للثمار الناضجة .